Overexpression of a peach CBF gene in apple: a model for understanding the integration of growth, dormancy, and cold hardiness in woody plants - Wisniewski, Michael; Norelli, John; Artlip, Timothy (Frontiers in Plant Science, 2015)
The timing of cold acclimation and deacclimation, dormancy, and budbreak play an integral role in the life cycle of woody plants. The molecular events that regulate these parameters have been the subject of much study, however, in most studies these events have been investigated independently of each other. Ectopic expression of a peach CBF (PpCBF1) in apple increases the level of both non-acclimated and acclimated freezing tolerance relative to the nontransformed control, and also inhibits growth, induces early bud set and leaf senescence, and delays bud break in the spring. The current study examined differences in the seasonal expression of genes (CBF, DAM, RGL, and EBB) that have been reported to be associated with freezing tolerance, dormancy, growth, and bud break, respectively, in the PpCBF1 T166 transgenic apple line and the nontransformed M.26 control. Results indicated that expression of several of these key genes, including MdDAM, MdRGL, and MdEBB was altered in transgenic T166 trees relative to nontransformed M.26 trees. In particular, several putative MdDAM genes, associated with the dormancy-cycle in other species of woody plants in the Rosaceae, exhibited different patterns of expression in the T166 vs. M.26 trees. Additionally, for the first time a putative APETALA2/Ethylene-responsive transcription factor, originally described in poplar and shown to regulate the timing of bud break, was shown to be associated with the timing of bud break in apple. Since the overexpression of PpCBF1 in apple results in a dramatic alteration in cold acclimation, dormancy, and growth, this transgenic line (T166) may represent a useful model for studying the integration of these seasonal life-cycle parameters.